Service provided by fading MIMO channels: a deterministic perspective. Issue 17 (22nd October 2012) - Dong, Yunquan; Fan, Pingyi; Letaief, Khaled Ben
ABSTRACT In this paper, we study the channel service process of a multiple‐input multiple‐output (MIMO) system over an independent and identically distributed (i.i.d.) fading channel. One key problem of communication over fading MIMO channels is what kind of service the MIMO channel can provide. In this paper, this problem is investigated in terms of channel service process. Assuming that the channel state information is available at the receiver, the channel service process S(t) is defined as the integral of the instantaneous channel capacity over a time interval of length t, which specifies the service provided by the channel during the period. Using the characteristic function approach and the infinitely divisible law, it is proved that the channel service process S(t) is a deterministic linear function of time t, other than any curve form or a stochastic process. Specifically, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdjvhb2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />S(t)=cmimo*⋅t</alternatives>, where <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdjvh8z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />cmimo*</alternatives> is a constant equal to the corresponding ergodic capacity. This result has two implications: (i) i.i.d. fading MIMO channels can support a constant rate traffic stream of rate <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdjvh6v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />cmimo*</alternatives> without higher layer transmission delay; (ii) the ergodic capacity is the actual transmission capacity of the fading channel, other than only a statistical average value. Copyright © 2012 John Wiley & Sons, Ltd.